Polymorphisms in Toll-like receptor genes and susceptibility to infections in allogeneic stem cell transplantation - Carvalho, Agostinho (2009)
Objective Discovery of genetic variations in the genes encoding for Toll-like receptors (TLRs) has highlighted a potential link between genomic variation of the host and susceptibility to infections. Materials and Methods We investigated the association between polymorphisms in the TLR2, TLR4, and TLR9 genes in recipients of allogeneic hematopoietic stem cell transplant and susceptibility to infections caused by cytomegalovirus and filamentous fungi. Results A significant association was observed between the presence of the T-1237C polymorphism (TLR9) and susceptibility to viral pneumonia (p = 0.04; odds ratio [OR]: 1.73). For fungi, a significant association was observed between the presence of the cosegregating Asp299Gly/Thr399Ile polymorphisms (TLR4) and fungal colonization (p = 0.003; OR: 10.6). However, susceptibility to fungal infections, predominantly fungal pneumonia, was instead significantly decreased in the presence of the same polymorphisms (p = 0.03; OR: 0.23). Conclusion Thus, fungal colonization may not predict susceptibility to infection in the presence of these single nucleotide polymorphisms. The finding that defective viral but not fungal sensing may predict susceptibility to infection highlights the divergent function of TLRs in the pathogenesis of opportunistic infections.